Experimental study on the motion response of an integrated floating desalination plant and offshore wind turbine on a non-ship platform. (15th August 2021) - Amin, Islam; Dai, Saishuai; Day, Sandy; Ali, Mohamed E.A.; Balah, Ahmed; Shawky, Hosam; Oterkus, Selda; Oterkus, Erkan
Abstract: An on-grid floating desalination plant (FDP), powered by conventional fossil fuel, was recently proposed to support freshwater demands in some remote coastal cities that have electricity grid networks. The aim of this study is to investigate feasibility of integrating a wind turbine into the same FDP platform to be suitable for off-grid services with sustainable clean energy resources. The new proposed concept is a fully self-contained mobile system powered by wind. Using a 1:100 scale model of the proposed concept, an experimental study was performed to investigate the floater's motion behavior in Egypt. According to historical sea statistical data for Red Sea in Egypt and taking combined dynamic responses of turbine and floating platform into consideration, frequency and time history dynamic analyses have been done. Furthermore, the possibility of using five different wind turbines in the same FDP platform was studied for upgrading purposes. Results show that the proposed FDP concept has capability to support all tested turbines and to operate safely in Egyptian environmental conditions. Based on the FDP concept with and without turbine comparisons, there are minor motion changes in heave responses, while pitch and surge responses show major changes in time history analyses due to turbine operation. Highlights: An integrated floating desalination plant and offshore wind turbine on a non-ship platform is considered. Experimental study on the motion response of the platform was performed. The possibility of using five different wind turbines in the same FDP platform was also studied for upgrading purposes. The platform has the capability to support all tested turbines and operate safely in Egyptian environmental conditions.